Effects of Different Types of Music on the Germination and Seedling Growth of Alfalfa and Lettuce Plants - You-Ning Lai; How-Chiun Wu (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
The aim of this study was to investigate the effects of music on lettuce and alfalfa seed germination and seedling growth. Nine music treatments were used: Control (no music); Gregorian Chant; Baroque; Classical; Jazz; Rock; Nature sound; New-age; Waltz. For the duration of the study, music was played for 12 hours each day for seven days. Results showed that a significantly lower number of alfalfa seeds germinated in the rock music treatment. In contrast, the highest percentage of alfalfa seeds germinated in treatments with music was those in the classical, nature sound, and waltz treatments. In lettuce seedlings, significantly longer radicles were observed in the Gregorian chant, new-age, and waltz treatments compared to the control, whereas no such effects were evident in alfalfa seedlings. Significantly longer lettuce hypocotyls were found in Gregorian chant, jazz, nature sound, new-age, and waltz music treatments. Of these, although exposure to jazz and nature sound significantly promoted the growth of lettuce hypocotyls, the growth of alfalfa hypocotyls was inhibited under identical conditions. Lettuce seedlings grown in Gregorian chant, new-age, and waltz music produced both significantly longer radicles and hypocotyls, and are suitable to be used as an alternative method to improve seedling growth and development.